Faktor-faktor Yang Mempengaruhi Harga Tipe Produk Mobil Honda Di Kota Parepare - Faradita, Afifah; Wahyuningsih, Sri; Anggreni, Renita; Zaudiah; Muyassarah M. As, Amalia (Jurnal Ilmu Manajemen, Bisnis dan Ekonomi, 2024)
The main objective of this service is to increase the economic literacy of the people of Parepare City regarding the factors that influence the price of Honda car products. able to understand the dynamics of the automotive market in more depth and make more rational purchasing decisions. The partner problem that will be resolved is a lack of understanding of the factors that influence prices, so that they can provide data-based recommendations to automotive industry partners. The research method used in the research is a descriptive qualitative approach with the research location in Parepare City. Activity participation involves official Honda dealers, consumers and automotive business players as key informants. Data was collected through in-depth interviews, field observations and documentation. The materials used were a list of interview guides and data recording tools. The problem solving method is carried out by identifying factors such as market conditions, marketing strategies, pricing policies and consumer preferences. that consumer preferences in Parepare City are influenced by a combination of economic, technical and emotional factors. An effective marketing strategy is one that is able to accommodate the needs of consumers from various segments, such as offering competitive prices, easy financing, and satisfactory after-sales service. Research shows that the price of Honda cars in Parepare City is influenced by various factors, including demographic characteristics, marketing strategies, and changes in market dynamics. Consumers who have diverse preferences drive dealers